2012
DOI: 10.1097/pec.0b013e31823ed6ca
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Implications of Adolescent Methamphetamine Exposures

Abstract: In this data set, adolescent methamphetamine exposures were associated with increased rates of suicidal ideation and suicide attempts that are disproportionate to population-based surveys during the same period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The experience of psychotic symptoms (delusions and auditory hallucinations) has been reported in over half of a sample of cannabis and cocaine substance abusers, either during the use or withdrawal of those substances (Smith et al, 2009). Dependent users of cocaine (Mahoney et al, 2008), opiates (Smith et al, 2009), methamphetamine (Srisurapanont et al, 2003; Auten et al, 2012) and cannabis (Arendt et al, 2005) also experience delusions and AVH (Smith et al, 2009), usually in over 50% of responses for each study. The severity of the psychotic symptoms are almost always significantly related to the rate of substance use, such that severity of psychotic symptomatology increased with increasing rate of dependence.…”
Section: Substance-induced Auditory Verbal Hallucinationsmentioning
confidence: 99%
“…The experience of psychotic symptoms (delusions and auditory hallucinations) has been reported in over half of a sample of cannabis and cocaine substance abusers, either during the use or withdrawal of those substances (Smith et al, 2009). Dependent users of cocaine (Mahoney et al, 2008), opiates (Smith et al, 2009), methamphetamine (Srisurapanont et al, 2003; Auten et al, 2012) and cannabis (Arendt et al, 2005) also experience delusions and AVH (Smith et al, 2009), usually in over 50% of responses for each study. The severity of the psychotic symptoms are almost always significantly related to the rate of substance use, such that severity of psychotic symptomatology increased with increasing rate of dependence.…”
Section: Substance-induced Auditory Verbal Hallucinationsmentioning
confidence: 99%
“…Recent studies have claimed that adolescents who took MA led to side effects in the neural system. 2,3 Researchers have confirmed that MA induces oxidative stress, inflammation, and apoptosis in the cerebral regions such as hippocampus, 4 6 but the underlying molecular mechanisms and signaling pathways involved in MA abuse remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion was well tolerated except for one episode of suicidal ideation, a known complication of antidepressants in adolescents, which also may have been triggered by the participant’s methamphetamine relapse [8]. Methamphetamine dependence and cravings, marijuana use, conduct disorder, ADHD, and depressive symptoms were more frequent in the bupropion than placebo group which may explain the poor outcomes observed in the bupropion group.…”
Section: Discussionmentioning
confidence: 99%